Safety and immunogenicity of a single dose of a tetravalent dengue vaccine with two different serotype-2 potencies in adults in Singapore: A phase 2, double-blind, randomised, controlled trial. Issue 6 (5th February 2020) - Tricou, Vianney; Low, Jenny G.; Oh, Helen M.; Leo, Yee-Sin; Kalimuddin, Shirin; Wijaya, Limin; Pang, Junxiong; Ling, Li Min; Lee, Tau Hong; Brose, Manja; Hutagalung, Yanee; Rauscher, Martina; et al.
Highlights: Both TAK-003 formulations showed an acceptable safety profile and were immunogenic. The TDV formulation appears to elicit a more balanced immune response than HD-TDV. In baseline seronegative subjects, response to DENV-2 was less dominant with TDV. DENV-4 seropositivity rates and GMTs were higher with TDV in these subjects. Abstract: Background: Early formulations of Takeda's tetravalent dengue vaccine candidate (TAK-003) have demonstrated notably higher neutralizing antibody responses against serotype 2 than other serotypes. Here, we assessed the immunogenicity and tolerability in adults living in Singapore of two TAK-003 formulations: an early formulation, referred to as HD-TDV, and a new formulation with 10-fold lower serotype 2 potency, referred to as TDV (NCT02425098). Methods: Subjects aged 21–45 years were stratified by baseline dengue serostatus and randomised 1:1 to receive a single dose of either HD-TDV or TDV. Immunogenicity was evaluated at Days 15, 30, 90, 180, and 365 post-vaccination as geometric mean titres (GMTs) of neutralising antibodies and seropositivity rates. Viremia was assessed per vaccine strain. Solicited and unsolicited adverse events (AEs) were assessed by severity and causality. Results: Of 351 subjects randomised, 176 received HD-TDV and 175 received TDV. Peak GMTs against all serotypes were observed at Day 30, with highest GMTs against DENV-2 in both groups. In subjects seronegative at baseline, the response to DENV-2 was less dominant with TDV (Day 30 GMTs: 813 for TDV, 10, 966 for HD-TDV). In these subjects, DENV-4 seropositivity rates and GMTs were higher with TDV (Day 30 GMTs: 58 for TDV, 21 for HD-TDV; seropositivity rates: 76% for TDV, 60% for HD-TDV). Viremia mainly occurred for TDV-2 in both vaccine groups, with a lower incidence in TDV recipients, and mostly resolved by Day 30. Both vaccine formulations showed an acceptable safety profile with similar overall rates of solicited and unsolicited AEs across vaccine groups. Conclusions: These results suggest a more balanced immune response with the new formulation TDV compared with the early formulation HD-TDV, particularly in subjects who were seronegative prior to vaccination, and support the choice of the new formulation for the phase 3 efficacy assessment.